Palermo open city. Cosmopolitan Habitat - Urban Design Studio. - (:unkn) unknown (My University, 2020)
The book explores how the idea of “Cosmopolitan Habitats” as a global vocation for inclusiveness can influence urban futures. Based on a research and study project and on an international workshop in Palermo, in cooperation with the Department of Architecture of the University of Palermo, PALERMO OPEN CITY asks how tangible and intangible cultural heritage can be conceived as a creative factor for productivity and openness. How can elements, energies, and networks of a collaborative city overcome spatial and social fragmentation? What role can boundaries, limits, borders, thresholds, and peripheries play for envisioning a “Cosmopolitan Habitat”?
Keywords: Stadtgestaltung; Städtebau; Stadtarchitektur; Quartierentwicklung; Entwurfsseminar; Workshop; Exkursion; Studienprojekt; Stadtentwicklungsforschung